2022
DOI: 10.2196/31992
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Evaluation of a Fear of COVID-19 Scale in China: Cross-sectional Study

Abstract: Background At the very beginning of the COVID-19 pandemic, information about fear of COVID-19 was very limited in Chinese populations, and there was no standardized and validated scale to measure the fear associated with the pandemic. Objective This cross-sectional study aimed to adapt and validate a fear scale to determine the levels of fear of COVID-19 among the general population in mainland China and Hong Kong. Meth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…The BCFS was previously validated in Chinese for COVID-19 fear measurement [22]. Similar to this study, the validation study of Choi and colleagues confirmed their convergent validity of BCFS for COVID-19 fear with the PHQ-4; correlations between the level of fear and anxiety and depressive symptoms were validated [22].…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The BCFS was previously validated in Chinese for COVID-19 fear measurement [22]. Similar to this study, the validation study of Choi and colleagues confirmed their convergent validity of BCFS for COVID-19 fear with the PHQ-4; correlations between the level of fear and anxiety and depressive symptoms were validated [22].…”
Section: Discussionsupporting
confidence: 80%
“…reliability) [22]. Therefore, it can be confirmed that BCSF, which was modified for measuring COVID-19 fear both in Korean and Chinese, is valid and reliable.…”
Section: Plos Onementioning
confidence: 74%
See 2 more Smart Citations
“…Furthermore, even though the Fear Scale was originally developed to measure fear of breast cancer, the question items are generic and comprehensive. The Fear Scale covers common responses to fear such as feeling scared, nervous, upset, depressed, jittery, uneasy, and anxious, as well as having heart palpitations (Choi et al, 2022). And finally, the 8-item Breast Cancer Fear Scale was one of the few instruments available to measure fear among the Turkish population (Secginli, 2012).…”
Section: Data Collection Toolsmentioning
confidence: 99%